Women Nurturing Community during Natural Disaster: a Study of the Ecology of Kudus Rahtawu Muria Mountain Village - Mochamad Widjanarko; Mamik Indaryani (Yayasan Jurnal Perempuan, 2015)
Participation to preserve, care and positive behavior in accordance with the insight wisdom in managing the real environment is closely rooted in the tradition of women. This study aims to determine the potential of women in the face of natural disasters and identify efforts by women to reduce vulnerability to natural disasters in Rahtawu village, Kudus. Several women’s steps that has been studies are: first, there are efforts to mitigate disaster though its shape is still individualized. Second, to strengthen disaster victims and the persistence of attitudes, women working together to cope with disaster by cooking together with the community